(3bUjOI aj GdQO Ydi QLd ef Cgd UfYGA hGab ePgHg ePgH GdOgGfs ((3GdSjO jGSjf Hf GdSjO EHQGgje GdHUQj GdMSjfj s)
(3ChdgG (B:s
(3HHOCJ HHSe Gddg hGdTcQ hGdMeO Ydi fYe LdJ GdMUQ hGdYO hHYO aai UfYGA bO HGf NGQL ehGJ HJVdjd eSjdeI GdfLO EdjfG CJJ ef Cgd fLO bUjOI dg YWdJ Ydi NdjI GdaVd hGdLO s
(3BNQgG (B:s
(3adG RGd Qcf GdOjf QcfkG eTjOkG hCQcGf efi YGOGg ai GdOc hGdYgO hUdi Ydi GdeHYhK ddfGS QMeI Bdg GdSeGA eG VGY YQa ai GdQfO hBd hCUMGH hSde OGFekG UdGI hJSdjekG jLdGf Yfg YO hGdMeO ddg hMOg Je s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs